Tinjauan Hukum Pidana Islam terhadap Pelaku Pemerkosaan Mayat - Azizi, Al-Yafie; Iwan, Iwan (Legal Standing : Jurnal Ilmu Hukum, 2025)
The criminal act of necrophilia is a rare phenomenon but has serious implications for the dignity of the deceased and human values. This study is motivated by the legal void in Indonesia’s Criminal Code (KUHP), which does not explicitly regulate this crime. However, the Draft Criminal Code (RKUHP) has begun to include provisions addressing inhumane treatment of corpses, including necrophilia. From the perspective of Islamic criminal law, this act is considered a severe violation of the sanctity of the deceased and religious values. The aim of this study is to examine the crime of necrophilia from the perspective of Islamic criminal law to provide theoretical insights and propose alternative legal regulations relevant to Indonesia. The study employs a normative juridical research method, using a statutory approach and an analysis of Islamic legal doctrines, particularly principles of ta'zir, diyat, and interpretations by Islamic scholars concerning the dignity of the deceased. The findings reveal that while Islamic criminal law does not explicitly regulate necrophilia, this act is classified as a serious offense violating the sanctity and dignity of the deceased. Punishments include ta'zir, which is left to the discretion of judges, and diyat as compensation to the victim's family. The study concludes that both Indonesia's positive law through the RKUHP and Islamic criminal law regard necrophilia as a grave offense requiring clear legal provisions and strict punishment. This research recommends strengthening legal regulations to protect the dignity of the deceased while reflecting the values of justice and humanity.